2009
DOI: 10.1099/mic.0.025981-0
|View full text |Cite
|
Sign up to set email alerts
|

Small heat-shock protein Hsp12 contributes to yeast tolerance to freezing stress

Abstract: The HSP12 gene encodes one of the two major small heat-shock proteins of Saccharomyces cerevisiae and is induced under different conditions, such as low and high temperatures, osmotic or oxidative stress and high sugar or ethanol concentrations. However, few studies could demonstrate any correlation between HSP12 deletion or overexpression and a phenotype of sensitivity/resistance, making it difficult to attribute a role for Hsp12p under several of these stress conditions. We investigated the possible role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…However, until now this protein family has hardly been investigated in fungi. In T. borchii and in yeast, several dehydrin-like proteins (Hsp12, Gre1, Sip18) have been described previously [43][44][45][46][47]. Recently, Wong Sak Hoi et al [34,35] identified three dehydrins (DprA, DprB and DprC) in the A. fumigatus genome that contribute to the protection against high pH, freezing, osmotic and oxidative stress.…”
Section: Discussionmentioning
confidence: 93%
“…However, until now this protein family has hardly been investigated in fungi. In T. borchii and in yeast, several dehydrin-like proteins (Hsp12, Gre1, Sip18) have been described previously [43][44][45][46][47]. Recently, Wong Sak Hoi et al [34,35] identified three dehydrins (DprA, DprB and DprC) in the A. fumigatus genome that contribute to the protection against high pH, freezing, osmotic and oxidative stress.…”
Section: Discussionmentioning
confidence: 93%
“…S3) (Pacheco et al, 2009;Welker et al, 2010). The HSP12 promoter contains several stress response elements (STRE) and was shown to be strongly induced following yeast exposure to diverse stress conditions (Martínez-Pastor et al, 1996;Pacheco et al, 2009). We have recently found that Hsp12 expression levels are tightly correlated to the expression of other Msn2 reporter genes, including PNC1 and TPS2, and to yeast stress survival, showing that HSP12 reporter gene can reflect overall Msn2 transcriptional activity (Sadeh et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…HSP12 is a general stress response gene encoding a plasma membrane protein and its expression is highly dependent upon Msn2/4 transcriptional activity (supplementary material Fig. S3) (Pacheco et al, 2009;Welker et al, 2010). The HSP12 promoter contains several stress response elements (STRE) and was shown to be strongly induced following yeast exposure to diverse stress conditions (Martínez-Pastor et al, 1996;Pacheco et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of sHSPs is considered part of the mechanisms responsible for tolerance to cold-stress injury in several organisms [61], [62]. The cold stress also induced a quick expression of AvHSP28.6 in sea anemone.…”
Section: Resultsmentioning
confidence: 99%